2′, 6′-Dimethylphenylalanine : A Useful Aromatic Amino Acid Surrogate for Tyr or Phe Residue in Opioid Peptides. (21st May 2012) - Sasaki, Yusuke; Ambo, Akihiro
Abstract : Two aromatic amino acids, Tyr 1 and Phe 3 or Phe 4, are important structural elements in opioid peptides because they interact with opioid receptors. The usefulness of an artificial amino acid residue2 ′, 6 ′ -dimethylphenylalanine (Dmp) was investigated as an aromatic amino acid surrogate for several opioid peptides, including enkephalin, dermorphin, deltorphin, endomorphin, dynorphin A, and nociceptin peptides. In most peptides, substitutions of Phe 3 by a Dmp residue produced analogs with improved receptor-binding affinity and selectivity, while the same substitution of Phe 4 induced markedly reduced receptor affinity and selectivity. Interestingly, replacement of Tyr 1 by Dmp produced analogs with unexpectedly high affinity or produced only a slight drop in receptor affinity and bioactivity for most peptides. Thus, Dmp is also a useful surrogate for the N-terminal Tyr residue in opioid peptides despite the lack of a phenolic hydroxyl group, which is considered necessary for opioid activity. The Dmp 1 -substituted analogs are superior to2 ′, 6 ′ -dimethyltyrosine (Dmt) 1 -substituted analogs for high receptor selectivity since the latter generally have poor receptor selectivity. Thus, Dmp is very useful as an aromatic amino acid surrogate in opioid peptides and may be useful for developing other novel peptide mimetics with high receptor specificity.